Dynamics of innovation in the production of cow milk in Ayotlán, Jalisco Mexico - Santos-Lavalle, Rodolfo; Flores-Verduzco, Juan José; Camacho-Vera, Joaquín Huitzilihuitl; Roldán-Suárez, Elizabeth; Islas-Moreno, Asael (Ecosistemas y Recursos Agropecuarios, 2023)
Small milk producers are very important, but they are the ones who face the greatest difficulties in remaining in business due to their low productivity and profitability. The objective was to carry out a diagnosis of milk production in Ayotlán, Jalisco, through the analysis of the dynamics of innovation and the identification of the main problem. The level of adoption of 30 technological and organizational innovations was calculated and the problem was identified through the construction of the problem tree, an analysis stage of the logical framework methodology. The incipient competitiveness was identified as the central problem of livestock farmers. The dynamics of innovation reveal that the causes are found in factors that depend on the technological and organizational management of the farmers, although they perceive the increasing price of inputs and the low prices paid for milk as causes, external factors that they do not control.
Keywords: Diffusion; Logical Framework; Organizational management; Small farmers; Technological management